2020
DOI: 10.3390/ijerph17072606
|View full text |Cite
|
Sign up to set email alerts
|

SettleIN: Using a Manualised Intervention to Facilitate the Adjustment of Older Adults with Dementia Following Placement into Residential Care

Abstract: The authors examined the feasibility of delivering an adapted version of SettleIN, a manualised staff-led programme designed to facilitate adjustment to care for new residents with dementia. The effects of SettleIN on resident adjustment, mood and quality of life were also investigated. A pilot randomised controlled trial was conducted. Nineteen new residents with dementia and 21 staff participants were recruited. Residents were randomly assigned to receive the SettleIN programme or residential care as usual. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…In terms of social behavior, one study indicated significant differences in favor of resilience interventions compared with controls ( 38 ). Meanwhile, no significant differences were found in neuropsychiatric symptoms ( 39 41 , 43 , 44 ), adjustment ( 26 ), stress ( 29 ), and anxiety ( 29 ) in favor of resilience interventions compared with controls. Besides, the results of other outcomes' assessments were inconsistent.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…In terms of social behavior, one study indicated significant differences in favor of resilience interventions compared with controls ( 38 ). Meanwhile, no significant differences were found in neuropsychiatric symptoms ( 39 41 , 43 , 44 ), adjustment ( 26 ), stress ( 29 ), and anxiety ( 29 ) in favor of resilience interventions compared with controls. Besides, the results of other outcomes' assessments were inconsistent.…”
Section: Resultsmentioning
confidence: 83%
“…Participants in most studies ( n = 10) were persons with dementia ( 26 , 28 , 29 , 38 , 41 44 , 46 , 47 ), one as persons with MCI ( 39 ), one as persons with MCI and early dementia ( 27 ), one as persons with dementia or cognitive impairment ( 45 ), and one was Alzheimer's ( 40 ). The number of participants ranged from 19 to 726, and seven studies had more than 100 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations